Phytoseiid mites of the tribe Typhlodromini (Acari: Phytoseiidae) from subSaharan Africa - Ueckermann, E.A.; Zannou, I.D.; Moraes, G.J. de; Oliveira, A.R.; Hanna, R.; Yaninek, John S. (2008)
This is the ninth publication in a series on the taxonomy of phytoseiid mites of sub-Saharan Africa. Sixty-five phytoseiidspecies of the tribe Typhlodromini Wainstein, all of which are in the genus Typhlodromus Scheuten are reported in this paper (62 in the subgenus Anthoseius DeLeon and 3 in the subgenus Typhlodromus Scheuten). They refer to all species of this tribe known to occur in sub-Saharan Africa. Fifteen new species are described and 41 species are redescribed. Most of the reported species were collected in various habitats in southern Africa and in cassava habitats in tropical Africa. A key is included for the separation of these species.